Evaluating Current Patterns of Assessment for Self‐harm in Emergency Departments: A Multicenter Study. (15th August 2013) - Caterino, Jeffrey M.; Sullivan, Ashley F.; Betz, Marian E.; Espinola, Janice A.; Miller, Ivan; Camargo, Carlos A.; Boudreaux, Edwin D.; ,; Gerson, Lowell
Abstract Objectives The objective was to describe self‐harm assessment practices in U.S. emergency departments (EDs) and to identify predictors of being assessed. Methods This was a prospective observational cohort study of adults presenting to eight U.S. EDs. A convenience sample of adults presenting to the EDs during covered research shifts was entered into a study log. Self‐harm assessment was defined as ED documentation of suicide attempt; suicidal ideation; or nonsuicidal self‐injury thoughts, behaviors, or both. Institution characteristics were compared relative to percentage assessed. To identify predictive patient characteristics, multivariable generalized linear models were created controlling for weekend presentation, time of presentation, age, sex, and race and ethnicity. Results Among 94, 354 charts, self‐harm assessment ranged from 3.5% to 31%, except for one outlying site at 95%. Overall, 26% were assessed (11% excluding the outlying site). Current self‐harm was present in 2.7% of charts. Sites with specific self‐harm assessment policies had higher assessment rates. In the complete model, adjusted risk ratios (aRR) for assessment included age ≥ 65 years (0.56, 95% confidence interval [CI] = 0.35 to 0.92) and male sex (1.17, 95% CI = 1.10 to 1.26). There was an interaction between these variables in the smaller model (excluding outlying site), with males < 65 years of age being more likely to be assessed (aRR = 1.14, 95% CI = 1.02 to 1.37). Conclusions Emergency department assessment of self‐harm was highly variable among institutions. Presence of specific assessment policies was associated with higher assessment rates. Assessment varied based upon patient characteristics. The identification of self‐harm in 2.7% of ED patients indicates that a substantial proportion of current risk of self‐harm may go unidentified, particularly in certain patient groups.